100 key research questions for the post‐2015 development agenda. (January 2016) - Oldekop, Johan A.; Fontana, Lorenza B.; Grugel, Jean; Roughton, Nicole; Adu‐Ampong, Emmanuel A.; Bird, Gemma K.; Dorgan, Alex; Vera Espinoza, Marcia A.; Wallin, Sara; Hammett, Daniel; Agbarakwe, Esther; Agrawal, Arun; et al.
Abstract : The Sustainable Development Goals (SDGs) herald a new phase for international development. This article presents the results of a consultative exercise to collaboratively identify 100 research questions of critical importance for the post‐2015 international development agenda. The final shortlist is grouped into nine thematic areas and was selected by 21 representatives of international and non‐governmental organisations and consultancies, and 14 academics with diverse disciplinary expertise from an initial pool of 704 questions submitted by 110 organisations based in 34 countries. The shortlist includes questions addressing long‐standing problems, new challenges and broader issues related to development policies, practices and institutions. Collectively, these questions are relevant for future development‐related research priorities of governmental and non‐governmental organisations worldwide and could act as focal points for transdisciplinary research collaborations.